Pre-registration midwifery education: is 'cleverness' the '7th C'?. (2nd April 2019) - Power, Alison; Siddall, Gillian; Mansfield, Sheryl
Abstract : Pre-registration midwifery education is vocational, requiring the teaching of specific skills and knowledge in preparation for a career as a midwife. In addition to being competent and confident in practice, student midwives are also expected to possess six fundamental values in order to deliver care of the highest quality: care, compassion, competence, communication, courage and commitment—known as the '6Cs'. This article will outline how the University of Northampton's midwifery team and colleagues in Library and Learning Services collaborate to support student midwives in their academic journey to develop sound academic skills, thereby nurturing the 7th C: 'cleverness'. Thanks to this partnership, students are aided to pass the programme of study with a BSc (Hons) degree and enter the workforce as a committed lifelong learner.